2010
DOI: 10.1080/13854040903266910
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the California Verbal Learning Test–II in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a disease of the central nervous system where roughly 50% of patients exhibit cognitive impairment. Episodic memory defects are particularly common in MS and the California Verbal Learning Test: 2nd Edition (CVLT-II) was recommended for assessment in MS in a recently published consensus position paper. We investigated the validity of the CVLT-II in 351 MS patients and 69 demographically matched normal controls. MS patients performed significantly more poorly on 18 of the 23 measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 33 publications
2
54
0
1
Order By: Relevance
“…Patients with MS often have difficulties with memory-the prevalence is reported between 40 and 65%. The most common verbal memory tests are tasks in which the patient learns a wordlist [16]. Visuospatial memory, too, is affected in patients with MS [13].…”
Section: Memory and Learningmentioning
confidence: 99%
“…Patients with MS often have difficulties with memory-the prevalence is reported between 40 and 65%. The most common verbal memory tests are tasks in which the patient learns a wordlist [16]. Visuospatial memory, too, is affected in patients with MS [13].…”
Section: Memory and Learningmentioning
confidence: 99%
“…In previous group studies, executive memory difficulties in MS have been widely reported [8,[26][27][28] and have generally been described as encoding impairments [8,23]. Some authors are operationalized this deficit as a pathological score for both cued recalls and delayed recognition [28,26], although a storage deficit could also explain this long-term profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, for all these scores, data reported in the literature are controversial. Discrepancies between studies cannot be explained in terms of sample sizes, since conflicting results have been reported both in relation to small (n<30 MS patients [28]; Randolph et al, 2005 [36] for examples) and large study samples (n>200, [8,37]). For similar disease durations (11.5 years), differences in the EDSS score may influence performances, but only when disability increases (no significant difference below and above 1.5 [25]; selective deficit for 4.7 group versus 2.8, [26]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations